(untitled) (Avocetta, 2018)
Italian Ornithological Commission (Italian Rarities Committee) - Report 27. This report covers the years 2016-2017 and presents the assessment results of 71 submission forms involving 47 taxa. The following 53 records, involving 35 taxa, were accepted, including 7 first records for Italy (Cat. AERC: A – COI List 1A, 1B): Blue-winged Teal Spatula discors (Emilia-Romagna 2015; 5th record); Green-winged Teal Anas carolinensis (Lombardy 2011; 4th record); Ring-necked Duck Aythya collaris (Piedmont 2016; 8th record); Black Heron Egretta ardesiaca (Apulia 2017; first record for Italy); Black-winged Kite Elanus caeruleus (six records: Calabria 2014, Friuli-Venezia Giulia 2015, Piedmont 2015, 2016, 2017, Abruzzo 2016; 9th-14th records); Levant Sparrowhawk Accipiter brevipes (three records: Latium 2014, Sicily 2015, 2015; 9th-11th records); Pacific Golden Plover Pluvialis fulva (two records: Veneto 2014, Lombardy 2017; 14th-15th records); Greater Sand Plover Charadrius leschenaultii (Latium 2015; 6th record); Red-necked Stint Calidris ruficollis (Sicily 2012; 2nd record); Baird’s Sandpiper Calidris bairdii (Latium 2015; 3rd record); Black-winged Pratincole Glareola nordmanni (Veneto 2017; 10th record); Sabine’s Gull Xema sabini (two records: Sicily 2016, Trentino-Alto Adige 2017; 10th-11th records); Laughing Gull Leucophaeus atricilla (Liguria 2014; 5th record); Franklin’s Gull Leucophaeus pipixcan (three records: Campania 2014, Apulia 2015, Sicily 2015; 3rd-5th records); Heuglin’s Gull Larus fuscus heuglini (Apulia 2012; 2nd record); Pied Kingfisher Ceryle rudis (Apulia 2014; first record for Italy); Blue-cheeked Bee-eater Merops persicus (Piedmont 2014; 15th record); Sooty Falcon Falco concolor (Sicily 2015; 3rd record); Isabelline Shrike Lanius isabellinus (Veneto 2015; 7th record); Steppe Grey Shrike Lanius pallidirostris (Calabria 2016; 5th record); Masked Shrike Lanius nubicus (Calabria 2017; first record for Italy); Iberian Chiffchaff Phylloscopus ibericus (two records: Sicily 2013, Lombardy 2016; 3rd-4th records); Eastern Bonelli’s Warbler Phylloscopus orientalis (Apulia 2015; 4th record); Dusky Warbler Phylloscopus fuscatus (two records: Apulia 2012, Emilia-Romagna 2017; 9th-10th records); Eastern Orphean Warbler Sylvia crassirostris (five records: Apulia before 1950, 2011-2014, 2016, 2016, 2017; 7th-11th records); African Desert Warbler Sylvia deserti (Sicily 2016; 6th record); Swainson’s Thrush Catharus ustulatus (Lombardy 2011; 4th record); Atlas Pied Flycatcher Ficedula speculigera (Sicily 2016; 2nd record); “Eastern” Black Redstart Phoenicurus ochruros phoenicuroides/rufiventris (Sicily 2015; first record for Italy); Moussier’s Redstart Phoenicurus moussieri (Sicily 2016; 10th record); North Caspian Stonechat Saxicola maurus hemprichii (two records: Sicily 2016, Latium 2017; first record for Italy - 2nd record); Pied Bush Chat Saxicola caprata (Tuscany 2017; first record for Italy); Whitecrowned Wheatear Oenanthe leucopyga (Latium 2017; 4th record); Blyth’s Pipit Anthus godlewskii (Sicily 2017; first record for Italy); Pallas’s Reed Bunting Emberiza pallasi (Sicily 2017; first record for Italy). The following record was accepted at the generic level only (COI List 1C): Isabelline/Red-tailed Shrike Lanius isabellinus/phoenicuroides (Calabria 2016; 3rd record). The following records were rejected (COI List 5A, 5B): Canvasback Aythya valisineria (Piedmont 2016); Black-browed Albatross Thalassarche melanophris (Liguria 2014); Brown Booby Sula leucogaster (Emilia-Romagna 2014); Spanish Imperial Eagle Aquila adalberti (Tuscany 2017); Baird’s Sandpiper Calidris bairdii (Sicily 2016); Pin-tailed Snipe Gallinago stenura (Emilia-Romagna 2013); Laughing Gull Leucophaeus atricilla (Tuscany 2012); White-rumped Swift Apus caffer (Sicily 2015); American Cliff Swallow Petrochelidon pyrrhonota (Sicily 2011); Dusky Warbler Phylloscopus fuscatus (Sicily 2013); “Eastern” Black Redstart Phoenicurus ochruros group “phoenicuroides” (two records: Latium 2009, Sicily 2014). Five records, not included here, are still pending a wider consensus. Systematic and nomenclature follow the Italian CISO-COI Checklist (http://ciso-coi.it/commissione-ornitologica-italiana). This new national list, that also includes subspecies, follows the taxonomy adopted by the IOC World Bird List (http://www.worldbirdnames.org/), as decided by the Committee in January 2018. For each species, the records are listed by date and information is given as follows: Italian and scientific name, the number of accepted records since 1950 and before that year (only the total figure in this summary), number of individuals if more than one, age or plumage and sex if known, location with the Province acronym in brackets, date, names of observers, and documentation (photograph, sound recording, skin etc.).